Exploring Attitudes and Strategies in L2 Writing: A Qualitative Study of EFL Students at Sebha University (Sirte University Journal of Humanities, 2025)
Writing in a second language involves both cognitive and affective challenges, yet limited research has explored the interaction of emotional and strategic factors among Libyan EFL learners. This study addresses this gap by examining students’ attitudes and strategies throughout the writing process. A qualitative design was employed using semi-structured interviews and classroom observations with Libyan university EFL students. The data were analyzed thematically to identify recurring patterns across participants’ emotional, strategic, and behavioral responses to writing tasks. Three central themes were identified: (1) emotional orientations toward writing, (2) strategic approaches to planning and revision, and (3) behavioral patterns before, during, and after writing. Participants reported a continuum of emotions from confidence to anxiety and employed diverse strategies such as outlining, freewriting, and audience awareness. Observational data confirmed consistent behaviors, including pre-writing preparation and post-writing reflection. The findings underscore writing as a complex process influenced by emotional, cognitive, and environmental factors. Pedagogically, the study highlights the need for instructional practices that integrate emotional support and strategic guidance to enhance EFL learners’ writing competence and confidence.
Keywords: Attitude; EFL; ESL; Writing process; Writing strategies